FIQH AL-AQALLIYYAT AS AN AMERICAN VERSION OF LOCAL WISDOM - Abas Mujiburohman (Khazanah: Jurnal Studi Islam dan Humaniora, 2018)
This article discusses a type of local wisdom in the field of Islamic legal culture that is developing among Muslims of the United States as they are minority in the country. Using Clifford Geertz’ and others’ understanding of law as part of culture, this article is arguing that the eventual religious tradition of a local community will grow from the convergence of varied traditions brought by individual Muslims from their cultures of origin. Following a process called territorialization, cultural interactions within a local community will result in the production of three religious traditions: the continuing, the improvised, and the suppressed traditions. Local practice as witnessed by the writer in his field research among Muslims of Lansing, Michigan is categorized as part of the second tradition. Further, this kind of local wisdom has been observed among American Muslim scholars. Among them is Taha Jabir Al-Alwani who has proposed the term fiqh al-aqalliyyat for the collections of new practices of Islamic teachings that are related to the status of Muslims being minority in the country.